2012
DOI: 10.1007/s00774-012-0377-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-osteopenic effect of alpha-ketoglutarate sodium salt in ovariectomized rats

Abstract: The purpose of the study was to determine the effect of alpha-ketoglutarate sodium salt (AKG) treatment on the mineralization of the tibia in female rats during the development of osteopenia (Experiment-1) and in the condition of established osteopenia (Experiment-2). Thirty-two female rats were ovariectomized (OVX) to induce osteopenia and osteoporosis and another 32 female rats were sham-operated (SHO) and then randomly divided between the two experiments. In Experiment-1, the treatment with AKG started afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…This thesis supports the observed μ‐CT analysis of trabecular bone tissue. Additionally, the character of changes in the structure of tibia diaphysis and its mechanical properties mimics our earlier observation in gonadectomized animals (Radzki, Bieńko, Filip, Albera, & Kankofer, ; Radzki, Bienko, & Pierzynowski, ). Yet, the lack of any influence of a snail meat‐based diet on the planar BMD of total skeleton and isolated tibia (DXA), as well as the vBMD of the cortical and trabecular compartments (pQCT) suggest the seen effects come about due to growth retardation.…”
Section: Discussionsupporting
confidence: 80%
“…This thesis supports the observed μ‐CT analysis of trabecular bone tissue. Additionally, the character of changes in the structure of tibia diaphysis and its mechanical properties mimics our earlier observation in gonadectomized animals (Radzki, Bieńko, Filip, Albera, & Kankofer, ; Radzki, Bienko, & Pierzynowski, ). Yet, the lack of any influence of a snail meat‐based diet on the planar BMD of total skeleton and isolated tibia (DXA), as well as the vBMD of the cortical and trabecular compartments (pQCT) suggest the seen effects come about due to growth retardation.…”
Section: Discussionsupporting
confidence: 80%
“…Studies using animal models have shown that dietary supplementation with AKG has favorable effects on energy status, protein synthesis, growth, and performance (Junghans et al, 2006;Hou et al, 2011;Dobrowolski et al, 2013;Yao et al, 2012) and can potentially prevent the development of several systemic diseases commonly found in the elderly (Kjellman et al, 1997;Harisson and Pierzhynowski, 2008;Niemiec et al, 2011;Radzki et al, 2012). Protective properties of AKG were also demonstrated in hyperammonemia, hyperaminoaciduria, or exposures to toxic nitrogen chemicals such as cyanide, ammonia, ammonium compounds, amines and hydrazines (Bhattacharya et al, 2002;Dakshayani et al, 2006;Bhattacharya et al, 2009).…”
Section: Alpha-ketoglutarate (Akg) Is An Important Intermediate In Thmentioning
confidence: 95%
“…It is possible that the consumption of snail meat as the sole source of protein causes effects similar to osteopenia or osteoporosis. The changes in the structure of the mandibles and their mechanical properties also resembled those in gonadectomized animals (24)(25)(26)28). In the last 20 years, a number of publications have demonstrated that the systemic bone mass loss that causes osteoporosis is highly correlated with the loss of teeth.…”
Section: Resultsmentioning
confidence: 96%
“…Dual X-ray absorptiometry (DXA) and peripheral quantitative tomography (pQCT) are the criterion standard for the evaluation and diagnosis of bone condition, They are very sensitive and reproducible techniques for measuring bone quality, not only in humans, but also in small animals (4,(25)(26)(27)(28). The quality of bone tissue is also measured by its resistance to fractures which occur when loads exceed the bone strength.…”
Section: Resultsmentioning
confidence: 99%